2012
DOI: 10.5463/dcid.v23i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Rights, Equality, Educational Provisions and Facilities for Students with Disabilities in Thailand: Legal and Practical Perspectives over the Past Decade

Abstract: This review aims to critically examine the present status of educational provisions and facilities for students with disabilities in Thailand, in accordance with the enforcement of various laws over the past decade (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although universities, both locally and internationally, may systematise support in slightly different ways, many universities follow similar trends to accommodate and support students with specific disabilities as per their needs. Cheausuwantavee and Cheausuwantavee (2012) argue that appropriate support systems in teaching and learning are vital in ensuring equal access for students with disabilities. The commitment of the institution to facilitating support and participation depends on its willingness to change admission, curricular and assessment procedures, as well as physical accessibility of the institution.…”
Section: Introductionmentioning
confidence: 99%
“…Although universities, both locally and internationally, may systematise support in slightly different ways, many universities follow similar trends to accommodate and support students with specific disabilities as per their needs. Cheausuwantavee and Cheausuwantavee (2012) argue that appropriate support systems in teaching and learning are vital in ensuring equal access for students with disabilities. The commitment of the institution to facilitating support and participation depends on its willingness to change admission, curricular and assessment procedures, as well as physical accessibility of the institution.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies indicate a wide gap between the policies and the educational services and practices experienced by children with disabilities (Cheausuwantawee and Cheausuwantawee 2012). There is evidence that concepts of policies and laws have not conformed to practice which affect the quality of teaching in inclusive classrooms (Vorapanya 2008;Cheausuwantawee and Cheausuwantawee 2012).…”
Section: Contextmentioning
confidence: 98%
“…There are inadequate numbers of teachers and educational staffs capable of teaching children with disabilities. Many teachers usually use the same content and management of curriculum for children without disabilities and usually control children with disabilities by using their own traditional or general education teaching plan (Cheausuwantawee and Cheausuwantawee 2012). This has resulted in a slow movement towards the realisation of full inclusion.…”
Section: Contextmentioning
confidence: 99%
“…Persons with disabilities in Singapore also highlighted the pressing need for greater public awareness (Raghunathan et al, 2015). Moreover, in a study conducted among Thai students, results showed that there seem to be ineffective policies and laws, poor management, and inequality of education resource allocation for people with disabilities (Cheausuwantavee & Cheausuwantavee, 2012).…”
Section: Introductionmentioning
confidence: 99%